Economic Policy of Palestine : Economic Policy and Institutional Reform for a Viable Palestinian state. - Cobham, David (Routledge, 2004)
How would Palestine organise itself as a state economically? A respected, international group of academics have come together under the editorship of Cobham and Kanafani to analyze and attempt to answer this difficult question.